Effect of Solvent Type and Germination Time on The Level of Free Amino Acid and Peptides of Germinated Pigeon Pea (Cajanus cajan (L.) Millsp) Extract - Ketut Ratnayani; Ni Wayan Wisaniyasa; Ni Putu Wiwik Oktayuni (The Journal of Pure and Applied Chemistry Research, 2022)
Germination can activate the degradation of storage protein in legumes releasing peptides and free amino acids for seed growth. These compounds have many benefits in many fields, especially in food and health. This study aimed to determine the effect of solvent type and germination time on the level of free amino acids (FAA) and the level of peptides (MW < 10 kDa) of germinated pigeon pea extract. The extraction of free amino acids and the dissolved protein from germinated pigeon pea flour was carried out using two kinds of solvents, namely water, and 0.1 N HCl. The variation of germination times of pigeon pea seeds was carried out at 12, 24, 36, 48, 60, 72, 84, and 96 hours. The level of FAA was determined spectrophotometrically using the ninhydrin method after the deproteination step, while the level of peptides was determined spectrophotometrically using the biuret method. The results showed that using 0.1 N HCl as a solvent produced a higher level of FAA and peptides in the extract than using water. The increase of germination time can increase the level of FAA with the peak FAA level achieved on 36 hours. The increase of germination time can increase the level of peptides with the peak of peptides level achieved on 84 hours of germination times. These results showed that seed germination is a potential method for producing free amino acids and peptides which accumulate at a specific time.